Relaxin modulates human and rat hepatic myofibroblast function and ameliorates portal hypertension in vivo. Issue 4 (3rd March 2014) - Fallowfield, Jonathan A.; Hayden, Annette L.; Snowdon, Victoria K.; Aucott, Rebecca L.; Stutchfield, Ben M.; Mole, Damian J.; Pellicoro, Antonella; Gordon‐Walker, Timothy T.; Henke, Alexander; Schrader, Joerg; Trivedi, Palak J.; Princivalle, Marc; et al.
<x xml:space="preserve">Abstract</x> Active myofibroblast (MF) contraction contributes significantly to the increased intrahepatic vascular resistance that is the primary cause of portal hypertension (PHT) in cirrhosis. We sought proof of concept for direct therapeutic targeting of the dynamic component of PHT and markers of MF activation using short‐term administration of the peptide hormone relaxin (RLN). We defined the portal hypotensive effect in rat models of sinusoidal PHT and the expression, activity, and function of the RLN‐receptor signaling axis in human liver MFs. The effects of RLN were studied after 8 and 16 weeks carbon tetrachloride intoxication, following bile duct ligation, and in tissue culture models. Hemodynamic changes were analyzed by direct cannulation, perivascular flowprobe, indocyanine green imaging, and functional magnetic resonance imaging. Serum and hepatic nitric oxide (NO) levels were determined by immunoassay. Hepatic inflammation was assessed by histology and serum markers and fibrosis by collagen proportionate area. Gene expression was analyzed by quantitative reverse‐transcription polymerase chain reaction (qRT‐PCR) and western blotting and hepatic stellate cell (HSC)‐MF contractility by gel contraction assay. Increased expression of RLN receptor (RXFP1) was shown in HSC‐MFs and fibrotic liver diseases in both rats and humans. RLN induced a selective and significant reduction in portal pressure in pathologically distinct PHT models, through augmentation of intrahepatic NO signaling and a dramatic reduction in contractile filament expression in HSC‐MFs. Critical for translation, RLN did not induce systemic hypotension even in advanced cirrhosis models. Portal blood flow and hepatic oxygenation were increased by RLN in early cirrhosis. Treatment of human HSC‐MFs with RLN inhibited contractility and induced an antifibrogenic phenotype in an RXFP1‐dependent manner. Conclusion: We identified RXFP1 as a potential new therapeutic target for PHT and MF activation status. (Hepatology 2014;59:1492‐1504)